Studies on Nd solubility in Ca10(PO4)6F2 and its borosilicate glass bonded analogues synthesized by using CaF2 recovered from spent salt of electro-winning process. Issue 22 (15th November 2021) - Shirley Auxilia, L.; Jena, Hrudananda; Parida, Sanjit Kumar
Abstract: Ca10 (PO4 )6 F2 (CaFAp) is one of the potential matrices for the immobilization of fluoride containing waste. Studies on the substitution of Nd to CaFAp are carried out to explore the solubility limit of Nd in CaFAp. A series of Ca10-x Ndx (PO4 )6 F2 with x = 0–1.2 compositions were synthesized by solid state reaction route. The product was found to form on heat-treatment at 973 K/4h in air. The product was characterized by X-ray diffraction (XRD), FTIR, Raman spectroscopy and thermo-gravimetric analysis followed by differential thermal analysis (TGA-DTA). Results obtained in this study shows the solid solubility limit of Nd is < 3 mol % in CaFAp, beyond which Ca3 (PO4 )2 phase was separated out as observed by XRD. However, its 20 wt % borosilicate glass bonded composite found to show 12 mol % Nd solubility. Normalized leach rate of Nd from Ca10-x Ndx (PO4 )6 F2, x = 0–0.3 matrix is found to be below detection limit (<0.1 μg/mL). However, the normalized leach rate for Ca 2+ and F −1 ions from the matrix was of the order of 10 −4 g cm −2 .day −1 and 10 −6 g cm −2 .day −1 respectively.